Modernization of Islamic Boarding School Education: Utilization of the Pintro Application System to Enhance Quality Management of Islamic Boarding School Services - Huda, Miftahul (IAIN Ponorogo, 2025)
This study aims to analyze and understand the utilization of the Pintro application system in response to the modernization at the Al-Hamidiyah Islamic Boarding School, Depok, in improving its service quality management. This study employed a case study qualitative research method. The data were collected using interviews, documentation, and observation. Data analysis from this study began with data presentation and reduction and ended with a conclusion. The result of this study affirms that the utilization of the pintro application system can respond to the challenges of modernizing the Al-Hamidiyah Islamic boarding school in Depok, by improving its service quality management. It involves registration services, student identity, number of students, students who win achievements and penalties, student learning progress, teacher profiles, learning curricula in madrasas and Islamic boarding schools, attendance of students and teachers, entry and exit permits for students, and even payment systems made digitally via virtual accounts.